The Influencee of Competence and Independence on the Audit Quality of the Inspectorate of the National Narcotics Agency of the Republic of Indonesia - Noorina Hartati; Anton Robiansyah (Journal of Economics, Business, and Government Challenges, 2021)
The purpose of this study is to provide empirical evidence about theinfluence of competence and independence on audit quality. The objects of thisresearch were the auditors who work at the inspectorate of the National NarcoticsAgency of the Republic of Indonesia. The data used in this study were primarydata in form of questionnaires which distributed to auditors at the Inspectorate ofBengkulu Province. The number of questionnaires which distributed was 48questionnaires. Some data were analyzed using multiple linear regression analysiswith the SPSS 18 program.The results of hypothesis test showed that the competence andindependence had a positive and significant influence on the quality of theinspectorate of the National Narcotics Agency of the Republic of Indonesia. Theresults of the study supported the theory of expectations and the previous researchwhich showed that competence had a positive effect on audit quality because thehigher the increase in competence, the higher the audit quality, and theindependence brought a positive effect on audit quality because the higher theindependence of auditors in BNN inspectorate of the Republic of Indonesia, itmade the auditors had better performance so that it would improve the auditquality.